Metabolic changes of phospholipids in animals fed with low selenium - LI Fang-sheng; WEI Feng-qun; BAI Qian-fu; GUAN Jin-yang; DUAN You-jin; ZOU Li-ming; ZHAO Yu-hua; LI Li; JIN Qun (Acta Pharmacologica Sinica, 2016)
Young guinea pigs and puppies were fed with semipurified diet with low Se and phospholipids. The blood Se and glutathione peroxidase activity were lowered, and the exjaled alkane and tissue chromolipid were elevated in guinca pigs fed with above-mentioned basal diet, and a diminished changes appeared in groups with supplementary Se. Se maintained the ratio between different composition of phospholipid in cartilage, but in the heart the ratio of phospholipids was improved only when adequate phospholipids (especiallyendogenous phospholipid) were given simultaneously. The membrane linking enzyme activity was slinghly restored by Se supplement. Only when both phosphlipids and Se were given sufficiently the cytochrome oxidase activity in myocardium and cAMP level in plasma increased markedly and even more than that of the control group.